NATURE BASED LIVING LAB (NB LAB): An undergraduate research experience at the Upper Amazonia. - Quishpe Quishpe, Luis Miguel (2024)
The Tena River basin is a partially explored biodiversity hotspot; however, it has been affected by anthropogenic activities and global warming. Observing the declines and extinctions in the wide range of Amazonian biodiversity before they went extinct is the primary purpose of research work in Ecuador. For this, complete information on the diversity of species coexisting in these areas is relevant because it enables the generation of strategies for conserving the environment and the species they harbor. Thus, the objective of the NB Lab 1 platform, Exploring the biodiversity of the Amazon landscape, was to contribute to the knowledge of the batrachofauna (amphibian assemblage) of the Tena River basin using DNA barcoding, environmental-DNA (eDNA) metabarcoding-based techniques, Nanopore sequencing, and automation of bioinformatics processes. This was carried out through three processes: 1) fieldwork: observation of specimens in their habitat and collection of environmental samples; 2) laboratory work: molecular assays for processing amphibian tissues and eDNA samples, library preparation, and ONT sequencing; 3) data analysis: use of bioinformatics tools such as NGSpeciesID for DNA barcoding data, amplicon_sorter for eDNA metabarcoding reads and bash for computational process automation. Forty amphibian 16S rRNA gene sequences were generated. The eDNA approach was used for biomonitoring amphibian populations, and four species were detected: Scinax ruber, Pristimantis malkini, Rhinella marina, and Pristimantis sp. Furthermore, a bash script based on the Linux platform was designed to reduce the data processing time of DNA barcoding and eDNA metabarcoding. Each biodiversity assessment project is a step towards a better knowledge of local biodiversity, which is fundamental at the governmental level to implement better management plans that further benefit local communities regarding environmental conservation.